Opioid Free Anesthesia During Sectio Caesarea Surgery in Pregnant Patients with Dengue Hemorrhagic Fever (A Case Report) - Dwipayana, I Made Agus Yudha; Pradhana, Adinda Putra (Syntax Corporation, 2024)
This study aims to evaluate the effectiveness of Opioid-Free Anesthesia (OFA) in maintaining hemodynamic stability and reducing side effects in emergency cesarean section patients. The background of this research lies in the high risk of opioid addiction and the rising death toll from opioid overdoses in the United States, along with common opioid-related side effects such as respiratory depression, ileus, and postoperative nausea and vomiting (PONV). The patient in this study is a 22-year-old woman at 38 weeks of pregnancy, in the latent phase of labor, with a history of fever due to Dengue infection without warning signs. The method used was general anesthesia without opioids, employing a multimodal pain management approach with non-opioid analgesics aimed at preemptively inhibiting pain receptors along the complex pain pathway, both centrally and peripherally. Results showed that OFA provided consistent hemodynamic stability from induction through to post-operation without any pain complaints, use of additional analgesics, or PONV. OFA effectively provides stable anesthesia and reduces the common side effects of opioids in patients, while supporting safe and efficient pain control without the risk of addiction. The study suggest that OFA with a multimodal approach is a viable option for perioperative anesthesia, reducing opioid dependency and associated side effects, and promoting patient safety in surgical procedures.